Performance Optimization - Alexander Mawuntu, Drixen; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This research was conducted to determine the influence of organizational culture and Employee Engagement on Employee Performance with Organizational Commitment as a Moderating Variable at the BPJS Employment Office, Medan City Branch and Sumbagut Regional Office. Organizations, both companies and government institutions, in carrying out their activities certainly need human resources that support efforts to achieve the goals set by the organization. The success of an agency/organization is not only determined by the facilities it has, but also the availability of reliable human resources. The results of this research are as follows: Organizational culture has a positive and significant effect on employee performance with an original sample value of 0.226 and an ap value of 0.015. Employee Engagement has a positive and significant effect on Employee Performance with an original sample value of 0.025. Organizational Commitment has a positive and significant effect on Employee Performance with an original sample value of 0.457 and ap value of 0.003. Organizational culture's influence on employee performance is moderated by organizational commitment with an original sample value of -0.218 and ap value of 0.045. Employee Engagement influences employee performance, moderated by Organizational Commitment with an original sample value of 0.098 and ap value of 0.228.